Maternal satisfaction with intrapartum care and associated factors among mothers who gave birth in public hospitals of the South West Shewa Zone, Ethiopia, 2022 - Tolesa, Fikadu; Alemu, Adugna; Beya, Moges; Feyisa, Mulugeta; Gezahagn, Andualem; Negash, Abdi; Shigign, Erean; Getaye, Asfaw; Negash, Abraham; Merga, Bacha (Frontiers in Global Women's Health, 2023)
Back-ground: Intrapartum care maternal satisfaction is a multidimensional assumption of satisfaction with self and with the physical environment of the delivery ward and quality of care. Maternal satisfaction with intrapartum care affects the selection of birthplace and helps in identifying gaps between actual and intended health care outcomes. This study aimed to assess factors that affect intrapartum care maternal satisfaction. Objectives: To assess intrapartum care maternal satisfaction and associated factors among mothers who gave birth in public hospitals, South-west Shoa Zone, Ethiopia, 2022. Methods: A cross sectional study approach among 420 mothers was conducted from April 14 – June 14, 2022. Systematic random sampling was used to select mothers for face–to–face interviews every two. The bivariate and multivariable logistic regression analyses were done. A p-values < 0.25 association study variables were transferred to multivariable logistic regression models. Adjusted odd ratio with their 95 % confidence interval was computed, and the p-value < 0.05 was considered statistically significant in the multivariable model. The results of this study were presented by using text, table, and chart. Results: A data were collected from 420 participants, and 413 mothers were completed the interview giving the response rate of 98.33%. The overall intrapartum care maternal satisfaction was 245 (59.32%) [95% CI: 55-64]. Mothers who were normal during labour and delivery (AOR = 2.57(95%CI: 1.30-5.07), labour duration persist 12 hours, and less (AOR=1.59(95% CI: 1.03-2.44), wait time < 15 minutes (AOR = 2.06(95%CI: 1.21-3.52) were significantly associated at p-value < 0.05 with intrapartum care. Conclusion and Recommendation: Greater than half of mothers were satisfied with overall intrapartum care. Health facilities managers and health care providers work hard together to improve intrapartum care maternal satisfaction.